Utilization of sweet potato flour in instant soup mix - Papa, Jeselle Montilla (2005)
ABSTRACT Sweet potato flour (SPF) has been tested previously in various food products to replace part of wheat flour (WF) in their formulations. These developments contribute to the possibility of cutting down the country's importation costs for WF. In this light, this study is aimed at utilizing SPF in instant soup mix (ISM) whereby its level of substitution for part of wheat flour is optimum as indicated by the ISM's high acceptability. Phase I dealt with the determination of the method to be used in producing SPF. Parameters considered were the products' color, maneuverability and yield as affected by the method's drying time and temperature. It also focused on the analysis for pH, moisture and soluble solids of the flour produced from the chosen method. Phase II involved three stages to determine the optimum level of SPF that can be substituted for WF in the ISM - (1) preliminary sensory evaluation of the overall acceptability of ISM samples with 0, 30, 50, 75 and 100% levels of SPF substituted for WF, (2) sensory evaluation of ISM samples with 0, 50, 75 and 100% levels of SPF substituted for WF, (3) sensory evaluation of ISM samples with 50, 65 and 75% levels of SPF substituted for WF. From the evaluations conducted, the 65% level of substitution was most acceptable and was found replicable. The dry ISM sample was then analyzed for pH and moisture while the reconstituted ISM sample was analyzed for viscosity. In Phase III, the raw material costs of the ISM with the original formulation and with 65% SPF were compared to determine if there is any difference and by how much.